A Study of Object Transparency Via Charge-Coupled Device Mathematical Modelling Assessment - Syarfa Najihah Raisin; Wan Zakiah Wan Ismail; Irneza Ismail; Sharma Rao Balakrishnan; Mus’ab Sahrim; Bushra Naeem; Farah Aina Jamal Mohamad; Ahmad Syahmi Mohd Zain; Abdullah Solihin Mohd Fauzi; Juliza Jamaludin (USIM Press, 2024)
MJoSHT2020, Volume 7, Special Issue, eISSN: 2601-0003